Using Electron-beam Resists as Ion Milling Mask for Fabrication of Spin Transfer Devices - Kyung-Ho Shin; Hoang Yen Thi Nguyen; Hyunjung Yi (한국자기학회, 2007)
Magnetic excitation and reversal by a spin polarized current via spin transfer have been a central research topic in spintronics due to its application potential. Special techniques are required to fabricate nano-scale magnetic layers in which the effect can be observed and studied. This work discusses the possibility of using electron-beam resists, the nano-scale patterning media, as ion milling mask in a subtractive fabrication method. The possibility is demonstrated by two resists, one positive tone, the ZEP 520A, and one negative tone, the ma-N2403. The advantage and the key points for success of this process will be also addressed.